The effect of strategic Entrepreneurship in improving the strategic position - an analytical study of the opinions of a sample of managers in private banks in the Middle Euphrates governorates - Akram Mohsen al-Yassiri; Adel Abbas Abdel Hussein (Iraqi Journal for Administrative Sciences, 2024)
The Study aims to tested the impact of strategic enterepreneurship to Achieve the Strategic niche, enalytic study of the views of a sample of employess in the private banks in provinces the middle al-furit, that have been selected communities to conduct the study in a total sample size (280) people representing leaders and workers in the private banks in the middle al-furit provinces. the study tried to answer several quations including what scenarios in the achievement of strategic niche most suited and the nature of the current situation of the banks studied in the light of its performance and practices . to answer the quations raised were built study on two major assumptions each included four hypotheses subset , in order to verify the authenticity of the hypotheses that have been built as well as data processing that emerged from the answers the study sample has been used to program the statistical (Excel 2010) , after the selection of statistical methods appropriate and consistent with the hypotheses of the study being (Nonparametrice). The importance lies the study to determined impact and relationship between independent variables is elements strategic entrepreneurship and between dependent variables is strategic niche, the study arrive at several from recommedations to strees necessity to strategic enterepreneurship effect framework good in strategic niche , In addition to benefit maybe from the in effect knowledge with significant in strategic entrepreneurship on a chieve the strategic niche, the study found a set of recommendations depend on the result of the study.